A STRUCTURALANALYSIS OF RUPI KAUR’S SELECTED POEMS IN THE SUN AND HER FLOWERS - Halimatus Saddiah; Rezky Khoirina Tarihoran (PHILOLOGY Journal of English Language and Literature, 2021)
Poetry, as a type of literary work, is a form of imaginative art that serves not only to entertain readers but also to educate or inform them about certain subjects. The primary data for this study came from Rupi Kaur's book The Sun and Her Flowers, specifically the poems Legacy, To Witness a Miracle, Timeless, Introvert, and Ode to Raymond Douillet'sA Short Tour and Farewell. The primary objective of this study was to ascertain the intrinsic and extrinsic elements present in the poems. Secondary data sources included journals and a few works of literature. The structural approach was chosen for this study because it is commonly used to describe intrinsic and extrinsic elements. This research employed a qualitative approach. The research discovered intrinsic elements such as theme, figurative language, diction, symbolism, and imagery, while extrinsic elements provided context for the poem's creation. This research was intended to serve as a guide for those interested in conducting research on the intrinsic and extrinsic elements found in poetry.